PENERAPAN KONSEP GEOGRAFI DALAM BUKU TEKS GEOGRAFI KELAS XI KURIKULUM MERDEKA TERBITAN KEMENTRIAN PENDIDIKAN KEBUDAYAAN RISET DAN TEKNOLOGI - Hamidah, Putri; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This research aims to analyze the application of geography concepts in geography textbooks for class XI of Kurikulum Merdeka published by Kemendikbudristek. This research uses qualitative and quantitative methods with literature studies. The research source used is the geography textbook for class XI of Kurikulum Merdeka published by Kemendikbudristek. The data was collected through documentation. The data analysis techniques used are percentage data analysis, content analysis, and qualitative analysis. According to the research, 40% of the 507 paragraphs in the geography textbook contain geography concepts. The textbook consists of four subject matter, one of which contains geography concepts with high criteria. The geography concept that dominates in this textbook is the concept of diversity and the concept of interaction. The concept of diversity is addressed in 72 paragraphs throughout the text, while the concept of interaction is mentioned in 106 paragraphs. Also, the concept of change is discussed in 21 paragraphs, whereas perception and representation are only present in 5 paragraphs. The application of organizing conceptually is predominantly observed in the second subject matter of the textbook. The textbook's application of conceptual geography concepts is still insufficient.